Analysis of the Impact Macroeconomic Variables on the Indonesian Sharia Stock Index (ISSI), 2019 - 2024 - Kurniyeh Kurniyeh; Farid Ardyansyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Abstract This research seeks to assess the extent to which macroeconomic indicators such as inflation, money supply, the BI Rate, and exchange rates affect the Indonesian Sharia Stock Index (ISSI). This study employs a quantitative method through data analysis using multiple linear regression techniques. the use of this method is made to determine the impact of the relationship between related variables. The data source in this study comes from secondary data available on the official website with a monthly time series data pattern starting from the period 2019 to 2024. The results of this study found that partially the ISSI is affected by inflation and exchange rates, this is evidenced by the negative results that show if inflation and value have a negative and significant effect. Compared to the money supply and BI Rate which shows a positive impact on the ISSI. On the other hand, through simultaneous tests it was found that the ISSI was simultaneously influenced by inflation, money supply, BI rate and exchange rate. This indicates that macroeconomic factors have an impact on the ISSI.